Hvilke ønsker har eldre med ikke-vestlig minoritetsbakgrunn for sin alderdom i Norge? - Johannessen, Berit; Hallandvik, Jan Erik; Steen, June Jacobsen (Nordisk tidsskrift for helseforskning, 2012)
This article is based on a qualitative study with interviews of ten elderly people with ethnic minority backgrounds. The purpose is to present what the elderly think and wish for their old age in Norway. Our study shows that the informants’ wishes for an old age in Norway are largely related to contact with their family and others from the same cultural background as themselves. But they also recognize that their collectivist family traditions changed in an individualistic direction and adapted to the values of the Norwegian majority culture. They stated that the Norwegian welfare state gives them a high degree of confidence, and they have an overriding desire to be integrated. It also means that the cultural competence of health workers in the public health service must be increased. There is no simple answer to the challenges we are faced with an increasing number of elderly people from ethnic minorities, but the Norwegian health policy makers can build on their wishes and use them in planning future care of the elderly, which measures the borderline between family care and public care may be applicable.